(untitled) (CIPEEX, 2023)
INTRODUCTION: Type 1 Diabetes Mellitus (T1DM) is characterized by a severe deficiency of insulin due to the destruction of pancreatic beta cells, associated with autoimmunity. It is more common in children and adolescents, but it can appear at any age. It presents clinically in a sudden manner, often with a propensity for ketosis and ketoacidosis, requiring full insulin therapy from the diagnosis. OBJECTIVE: The objective of this study is to evaluate the subacute responses of blood glucose and blood pressure in adults with type 1 diabetes after a session of strength exercises. METHODS: The sample will consist of 30 participants with Type 1 Diabetes Mellitus. Capillary blood glucose will be measured using a glucometer, and blood pressure will initially be measured during the pre-study evaluations on both arms, adopting the side with the higher value for the purposes of the research. RESULTS: The present project presented some limitations due to the execution process of the data collection stage, and it is estimated that its completion will occur by the end of 2023.